Efficacy of sputum induction from lower respiratory tract in children - Madeleine Ramdhani Jasin; Darmawan Budi Setyanto; Sri Rezeki Hadinegoro; Lisnawati Lisnawati; Pramita Gayatri; Nia Kurniati (Indonesian Pediatric Society Publishing House, 2015)
Background Although sputum is a good specimen for various examinations, such as cytology and microbiological culture, sputum induction (SI) is not a routine procedure in children. Objective To identify the efficacy of SI to obtain specimen from lower respiratory tract in children, identify side effects of SI, and the results of microbiological examination. Methods A cross sectional study was performed in children (aged 1 month to 18 years) who underwent SI. Sputum induction was performed by inhalation with hypertonic solution, consisted of salbutamol for 15 minutes continued with NaCl 3% solution for another 15 minutes. Sputum specimens were examined for number of alveolar macrophage cell, surfactant protein A (SP-A) concentration, also acid-fast bacili smear, and M. tuberculosis culture, or aerobic microbial culture. Results Forty subjects with lower respiratory tract infection participated in this study, and SI was succesfully performed in all subjects. Youngest subject was 2 month old, the eldest was 16 year 7 month old. Median duration of SI was 45 minutes, and majority of volume was 3 or 4 mL. Side effects were nosebleeds (40%) and vomiting (2.5%). Macrophage alveolar more than 5 cells in one specimen was found in 97.5% subjects. Surfactant protein A examination was performed in 30 specimens, and SP-A was detected in all specimens (median concentration 264.528 pg/ mL). Culture for M. tuberculosis was positive in 1 of 27 subjects, while acid fast bacili smear was negative in all examined subjects. Aerobic microbial culture was positive in 5 of 13 subjects. Conclusions Sputum induction has good efficacy in obtaining lower respiratory tract specimen and it is safe to perform in children. Specimen from sputum induction yields good positive result for aerobic microbial cultures.